Antimicrobial activities of citronella (Cymbopogon nardus) essential oil against several oral pathogens and its volatile compounds - Ahmad Kamal, Henny Zaliyana; Tuan Ismail, Tuan Nadrah Naim; Arief, Erry Mochamad; Ponnuraj, Kannan Thirumulu (Universitas Padjadjaran, 2020)
Introduction: Cymbopogon nardus is a strong aromatic plant with relevant medicinal properties due to its essential chemical compounds and its potential therapeutic effects. This study was aimed to evaluate the antimicrobial activities of citronella essential oil against several oral pathogens and to identify the volatile compounds. Methods: The essential oil of C. nardus was purchased from Excellent Wisdom Sdn. Bhd., Malaysia. The source of raw material was collected from Malacca, the southern region of Malaysia, and the company made its taxonomic identification. An experimental in-vitro study was conducted on the essential oil processed from C. nardus genus Cymbopogon of Poaceae family. The in-vitro antimicrobial activities of C. nardus essential oil were evaluated against Streptococcus mutans (ATCC 25175), Streptococcus sobrinus (ATCC 33478), and Candida albicans (ATCC 10231) using agar well diffusion assay. The identification of the volatile compounds was performed using gas chromatography-mass spectrometry (GC-MS). Results: The C. nardus essential oil exhibited inhibitory activity against C. albicans at the concentration of 6.25%, whereby the inhibitory activity against S. mutans and S. sobrinus began at the concentration of 25%. The antimicrobial activity of C. nardus essential oil was statistically significant at the concentration of 50% in all tested pathogens. The GC-MS analysis of the C. nardus essential oil revealed the presence of few constituents, which include monoterpenes, diterpenes, sesquiterpenes and phenolic compounds. Monoterpenes were the major identified terpenoids and contributed to 54.45% of the total volatile composition. The main identified monoterpenes were citronellal (11.35%), z-Citral (11.34%), β-Myrcene (6.70%), and β-Trans-ocimene (6.03%), which was the first time β-Myrcene and β-Trans-ocimene was found in high percentage. Conclusion: C. nardus essential oil is an active antibacterial agent against several oral pathogens, and the percentages of active volatile compounds are different within different origins.